Papyrology and the History of Early Islamic Egypt - Sijpesteijn, Petra,; Sundelin, Lennart, (Brill Book Archive Part 1, ISBN: 9789004472495., 2004)
Tens of thousands of documents dating form the late Byzantine and early Islamic periods have been found in Egypt. These texts, written on papyrus and a variety of other materials, in Greek, Coptic Egyptian, and Arabic, offer a unique, but underutilized resource for the study of a society experiencing a profound transformation, this volume collects papers given at the conference "Documentary Evidence and the History of Early Islamic Egypt", including editions of previously unpublished Greek, Coptic, and Arabic documents, historical and linguistic studies which make use of documentary evidence, a discussion of the importance of Arabic literary papyri, and an introduction to papyrology and its relevance for the study of this period of Egyptian history. For more titles about Papyrology, please click here.